SNPs in FNDC5 (irisin) are associated with obesity and modulation of glucose and lipid metabolism in Saudi subjects - Al-Daghri, Nasser M. (Lipids Health Dis, 2016)
BACKGROUND: Irisin is a recently identified myokine that plays an important role in preventing obesity and insulin resistance. We investigated whether the common FNDC5 (irisin precursor) gene variants influence susceptibility to obesity and type 2 diabetes (T2D) and verified the impact of FNDC5 gene variants on serum irisin levels, glucose and lipid metabolism in a Saudi population. METHODS: Genomic DNA from 814 (394 T2DM and 414 controls) subjects were genotyped for the five common SNPs (rs3480A/G, rs1746661G/T, rs1298190A/G, rs726344A/G and rs1570569G/T) of the FNDC5 gene using the TaqMan genotyping assay. Biochemical parameters and hematic concentrations of irisin and insulin as well as anthropometric indices were collected. RESULTS: Serum irisin levels were higher in T2DM patients compared to controls (p < 0.0001). Analyses of FNDC5 SNPs showed that: 1) The rs3480 GG associates with decreased risk of obesity (p = 0.005; odds ratio: 0.48) and lower body mass index (BMI) values (p = 0.03). In addition, GGAAG was identified as the protective haplotype against risk of obesity (p = 0.001; odds ratio: 0.23). 2) The rs1746661 G allele associates with higher triglyceride (TG) levels (p = 0.019). 3) The rs157069 TT genotype associates with higher fasting insulin (p = 0.029) and HOMA-IR (p = 0.002) as well as with lower circulating irisin levels (p = 0.016). CONCLUSIONS: SNPs in FNDC5 gene correlates with obesity and glucose-lipid metabolism possibly because they modulate the serum levels of irisin. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12944-016-0224-5) contains supplementary material, which is available to authorized users.